Handbook for homicide [large type] - Barrett, Lorna (Barrett, Lorna. Booktown mystery, 2021)
"Haven't Got A Clue bookshop owner Tricia Miles's relationship is on the rocks. After a not-so-fun vacation with her on-again-off-again lover, Marshall Cambridge, Tricia's hoping for smooth sailing back in Stoneham. Unfortunately Booktown greets her not with blue skies but with another body. When Tricia's assistant manager, Pixie, finds homeless vet Susan Morris's body behind Haven't Got A Clue, Pixie's checkered past makes her the prime suspect. Tricia sets out to clear Pixie's name armed with only an anchor insignia earring found at the scene of the crime. As Tricia digs deeper she discovers Susan was involved in a scandal right before retiring from the Navy-but since nobody in the village knows Susan, even Tricia's one lead is in danger of drying up. With family drama brewing in the background and all of Stoneham convinced her manager is a murderer, Tricia knows she has to get to the bottom of the case soon before Pixie's life is sunk"--